The use of antineuropathic medications for the treatment of chronic pain. Issue 3 (September 2020) - Urits, Ivan; Li, Nathan; Berardino, Kevin; Artounian, Kimberly Aleen; Bandi, Prudhvi; Jung, Jai Won; Kaye, Rachel J.; Manchikanti, Laxmaiah; Kaye, Adam M.; Simopoulos, Thomas; Kaye, Alan D.; Torres, Monica; et al.
Abstract : Chronic pain syndromes cost the US healthcare system over $600 billion per year. A subtype of chronic pain is neuropathic pain (NP), which is defined as "pain caused by a lesion or disease of the somatosensory system, " according to the International Association for the Study of Pain (IASP). The pathophysiology of neuropathic pain is very complex, and more research needs to be done to find the exact mechanism. Patients that have preexisting conditions such as cancer and diabetes are at high-risk of developing NP. Many NP patients are misdiagnosed and receive delayed treatment due to a lack of a standardized classification system that allows clinicians to identify, understand, and utilize pain management in these patients. Medications like tricyclic antidepressants, serotonin-norepinephrine reuptake Inhibitor (SNRIs), and gabapentinoids are first-line treatments followed by opioids, cannabinoids, and other drugs. There are limited studies on the treatment of NP.